A Collision Intrathyroidal Tumor Causing Primary Hyperparathyroidism: Evidence From an 18F-Choline PET/CT Study. (November 2021) - Foppiani, Luca; Sola, Simona; Pitto, Francesca; Ansaldo, Gianluca; Piccardo, Arnoldo
Abstract : Abstract: A 67-year-old man was diagnosed with primary hyperparathyroidism and normofunctioning left nodular goiter. Fine-needle aspiration cytology showed thyroid (Thy) 4 (suspicious of malignancy). After first-line imaging proved negative, integrated 18 F-choline PET/4D contrast-enhanced CT revealed uptake by the thyroid nodule and by 3 nodules of the left central compartment. Thyroidectomy and lymphadenectomy were performed. Histopathology revealed a collision tumor (ie, 2 histologically distinct tumors occurring at the same anatomic site) composed of both PTC (papillary thyroid carcinoma) and parathyroid carcinoma within the left thyroid nodule. Lymph nodes showed PTC metastases. Primary hyperparathyroidism and calcium levels normalized, and the patient underwent radioiodine therapy.